Implementasi Pengelolaan Dana Tazir pada KSPPS Nusa Bangsa Sejahtera Jawa Timur - Yayuk Muhsinah, Devi; Ahmad Subhan, Moh.; Rijal, Akmalur (Journal of Islamic Economics Studies and Practices, 2023)
This research is based on the background of customers who are late in paying because these customers are able to delay payment delays, which is a risk that Islamic financial institutions deliberately experience in doing financing where the risk must be minimized for the sake of financial institutions. And in controlling this control, Islamic financial institutions apply late fees or called ta'zir. And in controlling this control, Islamic financial institutions apply late fees called ta'zir. This study uses a qualitative research type. The results of the study show that at KSPPS Nusa Bangsa Sejahtera, East Java, ta'zir is applied to customers who are late in paying because these customers are able to delay payments intentionally, and funds originating from ta'zir funds or funds for delays in paying installments are included in social funds. , because the funds are not included in the pure income of the Nusa Bangsa Sejahtera KSPPS East Java, then the funds are managed and distributed in the form of social activities, as for the form of social activities in the form of donations to IPNU-IPPNU activities, Ansor, Youth Organizations, and also scholarships for educational institutions at LPBA Nurul Huda Lowayu Dukun Gresik. The analysis conducted by KSPPS Nusa Bangsa Sejahtera East Java is in accordance with the DSN fatwa no. 17/DSN-MUI/IX/2000 concerning sanctions on customers who are able to procrastinate.